Doping Effect on Structure, Optical, & Sensing Properties of Nanocrystalline (SnO2) Thin Films Prepared by Chemical Bath Deposition (CBD) Technique - Selma M.H. AL-Jawad; Amel S. Sabr; Abdulhussain K. Elttayef (Engineering and Technology Journal, 2016)
Thin films of Nanocrystalline Tin Oxide SnO2 and SnO2: Cu have been prepared on glass substrates using Chemical Bath Deposition (CBD) technique, The thickness of the deposited film was of the order of (300) nm . The films annealing in air at temperature 500◦C for 60 min .Structural, optical and sensing properties were studied under different preparation conditions like Cu-doping concentration (2%, 4% and 6%). These prepared films are polycrystalline with a tetragonal & orthorhombic crystal structure. The crystallinity and the particle size of the prepared samples were analyzed by X-ray diffraction (XRD), the results indicated the particle size of the prepared samples decreased with the increase of Cu doping concentrations some of the structure properties are changed by the addition Cu concentrations as dopants. The films are preferentially oriented along the (110) direction. We have got some surface morphology by Scanning Electron Microscopy (SEM), the results show decreasing of particle size with increasing doping concentration. The films have moderate optical transmission from (65% up to 88% at 800 nm), and the transmittance, absorption coefficient and energy gap were measured and calculated with Cu doping concentration. The results show that the doping caused to decreased the transmittance and energy gap from (3.55 to 3.8) eV while it caused to increase the absorption coefficient. It has also been found that Cu doped nanocrystalline SnO2 thin films gas sensing & recovery time material was presented a better sensitivity to CO gas compared to the pure SnO2.